Improving hydrogen evolution reaction and capacitive properties on CoS/MoS2 decorated carbon fibers. (6th March 2020) - Sangeetha, D.N.; Krishna Bhat, D.; Senthil Kumar, S.; Selvakumar, M.
Abstract: We report a facile method to transform abundantly dumped banana stem fibers into carbon fibers (CFs) useful for energy applications. The CFs surface area is increased by varying the quantity of KOH activation to 488 m 2 g -1 . The solvothermal method is used to synthesize CoS, CoS/MoS2 and also grown on the activated carbon fibers (ACFs). Nano nodules of CoS arranged into sheets and layers of MoS2 stacked together were found in FESEM analysis. The morphology of the CoS/MoS2 differs when grown on ACFs. The growth of CoS/MoS2 along the ACFs length prevents any stacking of the pseudocapacitance materials. The ternary composite ACFs/CoS/MoS2 exhibits superior supercapacitor behavior as well as hydrogen evolution reaction (HER) due to the synergetic effect of the conducting ACF surface and redox active CoS/MoS2 . A maximum specific capacitance of 733 Fg -1, energy and power density of 33 WhKg −1 and 999 WKg -1 respectively are obtained. A low Tafel slope value of 61 mVdec −1 is obtained for the ACFs/CoS/MoS2 ternary composite electrode. The present work therefore offers a fresh insight into the effective conversion of waste materials into electrode material for energy storage and conversion applications. Highlights: High surface area carbon fibers synthesized from banana fibers. Nano CoS/MoS2 grown on ACFs for enhanced supercapacitor and hydrogen evolution. High capacitance of 733 Fg-1 at 0.5 Ag -1 obtained for symmetric combination. Tafel slope of 61 mVdec −1 found for the ACFs/CoS/MoS2 composite.